Elevated Circulating IL-1β and TNF-Alpha, and Unaltered IL-6 in First-Trimester Pregnancies Complicated by Threatened Abortion With an Adverse Outcome - Nicolaos Vitoratos; Constantinos Papadias; Emmanuel Economou; Evangelos Makrakis; Constantinos Panoulis; George Creatsas (Mediators of Inflammation)
The purpose of the present study was to examine the profile of selected proinflammatory cytokines in maternal serum of first-trimester pregnancies complicated by threatened abortion (TACP) and its relevance to obstetric outcome. Serum levels of Th1-type cytokines interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-alpha), and Th2-type cytokine interleukin 6 (IL-6) were measured, by ELISA, in 22 women with TACP and adverse outcome at admission (group A) and compared with the corresponding levels of 31 gestational age-matched women with TACP and successful outcome at admission (group B1) and discharge (group B2) and 22 gestational age-matched women with first-trimester uncomplicated pregnancy (group C) who served as controls. Mann-Whitney U or Wilcoxon test was applied as appropriate to compare differences between groups. IL-1β and TNF-alpha were detected with significantly higher levels in group A, compared to all other groups. On the contrary, IL-6 levels were detected with no significant difference among all the other groups studied. It is concluded that in first-trimester TACP with adverse outcome, a distinct immune response, as reflected by elevated maternal IL-1β, TNF-alpha, and unaltered IL-6 levels, is relevant to a negative obstetric outcome.